Between the 'sectional' and the 'national' : oil, grassroots discontent and civic discourse in Nigeria - Akpan, Wilson Ndarake (Rhodes University, Faculty of Humanities, Department of Sociology, 2006)
This thesis examines the social character of petroleum-related grassroots struggles in Nigeria's oil-producing region. It does this against the background of the dominant scholarly narratives that portray the struggles as: a) a disguised pursuit of an ethnic/sectional agenda, b) a 'minority rights' project, and c) a minority province's protest against 'selective' environmental 'victimisation' by the majority ethnic nationalities. While the dominant scholarly analyses of the struggles are based on the activities of the better known activist organisations operating in the oil region, this thesis focuses primarily on the everyday 'grammar' of discontent and lived worlds of ordinary people vis-Ã -vis upstream petroleum operations and petroleum resource utilisation. The aim has been to gain an understanding of the forces driving community struggles in the oil region and their wider societal significance. Examined alongside the narratives of ordinary people are the legal/institutional framework for upstream petroleum operations and the operational practices of the oil-producing companies. Using primary data obtained through ethnography, focus group discussions, in-depth interviews and visual sociology, as well as relevant secondary data, the researcher constructs a discourse matrix, showing how grassroots narratives in selected oilproducing communities intersect with contemporary civic discourses in the wider Nigerian context. The thesis highlights the theoretical and policy difficulties that arise when the social basis of petroleum-related grassroots struggles and ordinary people's narratives are explained using an essentialist idiom. It reveals, above all, the conditions under which so-called 'locale-specific' struggles in a multi-ethnic, oil-rich African country can become a campaign for the emancipation of ordinary people in the wider society. This research extends the existing knowledge on citizen mobilisation, extractive capitalism, transnational corporate behaviour, and Nigeria's contemporary development predicament. It sheds light on some of the processes through which ordinary people are forcing upon the state a change agenda that could drive the country along a more socially sensitive development and democratisation trajectory.
Keywords: Petroleum industry and trade -- Nigeria; Revenue -- Nigeria; Nigeria -- Social conditions; Nigeria -- Economic conditions; Niger River Delta (Nigeria) -- Environmental conditions